Derivation of strategic solution space for product redesign planning - Romli, Fairuz Izzudin; Mohd Rafie, Azmin Shakrine (Praise Worthy Prize, 2011)
Planning for product redesign could become an overwhelming task due to possible change effects propagation phenomenon, particularly for complex product designs. However, it is observed that the solution space during redesign planning is normally constrained by product manufacturers. This leads to the notion that substantial amount of redesign efforts could be saved if designers are assisted to strategically define the solution space for their product redesign. This paper proposes a structured methodology to achieve this goal. Potential benefits of the proposed methodology have been demonstrated by the presented aircraft redesign case study.